Table 3_cAMP-MFN2 signaling suppresses cochlear cell senescence and age-related hearing loss.docx - Yu Liu (6938) (2025)
Introduction Age-related hearing loss (presbycusis) is the most common sensory deficit in the elderly, yet it lacks effective pharmacological treatments. The decline of the cyclic AMP (cAMP) signaling pathway is implicated in aging, but its functional role in the auditory system remains largely unknown. Methods To investigate whether enhancing cAMP signaling could counteract presbycusis and elucidate the underlying molecular mechanism, we used a D-galactose-induced cellular senescence model and an in vivo aged mouse model. The effects of the cAMP analog dibutyryl-cAMP (dbcAMP) on cellular senescence, inflammation, mitochondrial function, and cochlear structure were evaluated. The role of Mitofusin-2 (MFN2) was further assessed using siRNA-mediated knockdown. Results dbcAMP potently suppressed cellular senescence and the associated inflammatory phenotype. In addition, cAMP treatment alleviated mitochondrial dysfunction, as indicated by improved mitochondrial bioenergetics and morphology. The anti-senescence effects of cAMP were significantly blunted upon siRNA-mediated knockdown of Mfn2, establishing MFN2 as a key, though perhaps not the sole, component of this protective pathway. Importantly, systemic administration of dbcAMP to aged mice significantly preserved hearing function and protected cochlear hair cells. This in vivo protection was accompanied by an upregulation of cochlear MFN2 and a coordinated suppression of senescence and inflammation markers. Discussion Our study reveals a critical protective role for the cAMP-MFN2 axis in auditory aging by suppressing cellular senescence. These findings identify this axis as a novel and promising therapeutic target for the treatment of age-related hearing loss.